Patron-client relationships as a mechanism of public policy corruption - Abdalgader Mohamed Albasher Aboksawi; Afifuddin Afifuddin; Taufiq Rahman Ilyas (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
This study aims to uncover corruption related to public policy that focuses on patron-client relationships. The method used in this study is a literature review. Researchers use secondary data in journals, books, and related articles to discuss the problems researchers discuss. This study shows that political policy corruption is one example of political corruption that assumes that a person's position can bring benefits. These two elements are elements that strengthen and support each other. Political corruption will not occur without a patron-client relationship. Likewise, patrons will not be strong if they are not supported by political corruption. Second, patrons who come from regional heads tend to abuse their power. Patrons will use their authority to impose their will on others. This mechanism occurs because of the patron-client relationship carried out by political officials with informal actors. This relationship has a very significant impact on harming the state. The scientific contribution produced in this study is to explain more clearly the existence of public policy corruption manifested by political corruption